Rhomboid-like 2 correlated with TME infiltration inhibits cuproptosis-related genes and drives malignant phenotype in clear cell renal cell carcinoma - Zhifei Che; Wenyi Jin; Yaoxi Wu; Haoyong Li; Peiyu Liang (Scientific Reports, 2024)
Abstract The crosstalk between cuproptosis and the tumor immune microenvironment (TIME) is vital during clear cell renal cell carcinoma (ccRCC) malignant progression. However, the underlying molecular mechanisms regulate this cross-talk remain elusive. Through tailored machine learning, we analyze clinical ccRCC data from The Cancer Genome Atlas (TCGA) to explore the critical factors that regulate the interaction among cuproptosis, TIME, and tumor progression. We found that rhomboid-like 2 (RHBDL2), critical gene affecting this process, might inhibit cuproptosis-related genes (CRGs) and promotes ccRCC progression through the Wnt/β-catenin pathway. Next, knocking down RHBDL2 expression increased the cuproptosis-related genes ferredoxin 1 (FDX1) and lipoic acid synthase (LIAS) levels but reduced forkhead box P3 (FOXP3) levels and tumor growth in vivo and in vitro models. By employing HLY78, Wnt/β-catenin pathway activator, we rescued the expression of CRGs and the malignant proliferation and metastasis capacity in ccRCC cells with RHBDL2 knockdown. Mechanistically, RHBDL2 inhibits cuproptosis and promotes malignant progression of ccRCC through the Wnt/β-catenin pathway. Abnormal RHBDL2 expression may cause the suppressive TIME formation by regulating Treg-cell infiltration, thus triggering immune escape. In summary, our results indicated that RHBDL2 is an oncogene that induces tumorigenesis and targeting RHBDL2 may be novel therapeutic direction for metastatic ccRCC.